Starting points of national literature and culture (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2016)
This is a report of the international conference on Comparative Literature and Culture, organized by the Azerbaijan Comparative Literature Association and the Azerbaijani Literature Department of the Baku Slavic University.